Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1182/blood.v91.7.2588.2588_2588_2600
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoid Reconstitution After Autologous PBSC Transplantation With FACS-Sorted CD34+ Hematopoietic Progenitors

Abstract: T-cell and B-cell reconstitution was studied in nine patients who received fluorescence activated cell sorter (FACS)-sorted autologous CD34+ hematopoietic progenitor cells (HPC). The mean numbers of T cells (CD3+), B cells (CD19+) and CD34+ HPC administered to each patient were .004, .002, and 1.8 × 106 cells/kg, respectively. After high-dose myeloablative chemotherapy (busulfan, cyclophosphamide, etoposide) CD34+ HPC were infused and lymphoid reconstitution was monitored using flow cytometry and reverse trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
51
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 24 publications
7
51
1
Order By: Relevance
“…In our study we showed that CD34 + selection as a purging method did not compromise the time needed for ANC recovery compared with the unpurged group. This finding correlates with the results in previous studies documenting similar neutrophil recovery between unmanipulated and CD34 + -selected autologous grafts (Bomberger et al, 1998;Vescio et al, 1999). However, it is noteworthy that most patients who developed CMV DNAemia in the immediate post-transplantation period had received a graft with CD34 + cell selection, indicating delayed T-cell reconstitution compared with that in non-manipulated grafting.…”
Section: Discussionsupporting
confidence: 92%
“…In our study we showed that CD34 + selection as a purging method did not compromise the time needed for ANC recovery compared with the unpurged group. This finding correlates with the results in previous studies documenting similar neutrophil recovery between unmanipulated and CD34 + -selected autologous grafts (Bomberger et al, 1998;Vescio et al, 1999). However, it is noteworthy that most patients who developed CMV DNAemia in the immediate post-transplantation period had received a graft with CD34 + cell selection, indicating delayed T-cell reconstitution compared with that in non-manipulated grafting.…”
Section: Discussionsupporting
confidence: 92%
“…Depletion of substantial numbers of T cells from the grafts and a persistent decrease in CD4 + lymphocytes following CD34 + cell transplants may have predisposed these patients to viral infections. Highly purified CD34 + grafts may also result in a posttransplant reduction of the diversity of the peripheral T-cell repertoire compared to unmanipulated graft [26].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Associated risks of high-intensity regimens, however, preclude broader use of this approach in spite of its capacity to dramatically diminish new focal inflammatory disease activity in the central nervous system (CNS) of MS patients, who are otherwise treatment refractory. [11][12][13][14][15] Hence, elucidating the immune mechanisms underlying the therapeutic effect of high-intensity HSCT could guide development of more selective treatments with a more favorable risk/benefit profile.…”
mentioning
confidence: 99%